From Sengoku to Sexy: How Japanese Culture is Preserved in Anime. - Richieri, Julia L. (Tufts University. Tisch Library., 2015)
Tisch Library Undergraduate Research Award Winner, 2012. As time moves on, technology inevitably advances. With this comes new ways of recording, understanding, and transforming the past. In Japan, folktales and traditional stories are a huge part of culture. These stories were passed down orally at first, then on paper handscrolls. When these scrolls became obsolete, the stories moved to woodblock prints, and then to children’s books in the more modern era. Now, as printed text loses its appeal to children, how are traditional stories and legends to be preserved? Strange though it may seem, anime just might hold the answers. If we consider the ways in which Japanese animation preserves history, albeit adjusted to be understood by a modern viewer, popular television shows and videogames become more than simply Saturday morning cartoons.